THE EFFECT OF LIQUIDITY, SALES GROWTH AND PROFITABILITY ON DEBT POLICY (Case Study of Food and Beverage Sub Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2016 - 2018) - Rini Afnaini; Rahmawati Rahmawati; Irfan Tanjung (Jurnal Riset Manajemen Indonesia, 2021)
The purpose of this research is to determine the effect of Liquidity (CR), Sales Growth and Profitability (ROA) on Debt Policy in Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period, which is as much. The population in this study were all Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, as many as 26 companies. The technique used in sampling is purposive sampling method, the sample in this study was selected as many as 15 companies. Hypothesis testing uses multiple linear regression analysis using SPSS 23.00 for windows. The results of the study simultaneously Liquidity (CR), Sales Growth, and Profitability (ROA) have an overall influence on Debt Policy (DAR). Meanwhile, partially, the variable that has an effect on Debt Policy is Liquidity (CR).